Obesity modulates Alzheimer's disease through accelerated immune ageing. (December 2021) - Suzzi, Stefano; Croese, Tommaso; Ravid, Adi; Clark, Abbe R; Medina, Sedi; Colaiuta, Sara P; Vernon, Katherine; Gold, Or; Malitsky, Sergey; Itkin, Maxim; Cahalon, Liora; Greka, Anna; et al.
Abstract: Background: Emerging studies in Alzheimer's disease (AD) have identified, among numerous risk factors, immune dysfunction and midlife obesity. Here, we hypothesized that these two elements might be linked. Method: AD‐prone 5xFAD mice at 2 months of age were switched to a high‐fat diet (HFD, 60% calories from fat) for 28 weeks to induce obesity. As controls, we used 5xFAD mice fed a control diet (CD, 20% calories from fat). WT littermates for both diet groups were included in the study. We assessed cognition using the novel object recognition task until capturing divergence between the 5xFAD diet groups. Upon culling, the following tissues were harvested for analyses: brain (right hemisphere), for histopathological examination and ELISA; hippocampus (left hemisphere), for single‐nucleus RNA sequencing (sNuc‐seq); spleen, for flow cytometry and cytometry by time‐of‐flight (CyTOF); and plasma, for metabolic and non‐targeted polar metabolite screening. Result: HFD induced obesity accelerated cognitive deterioration, neuronal loss, and brain gliosis in 5xFAD mice, without altering amyloid β content. HFD had no effect on either cognition or brain phenotype in WT mice. sNuc‐seq of the hippocampus revealed a diet‐induced signature in oligodendrocytes, but did not detect changes beyond the AD‐associated signatures in microglia and astrocytes. Obese 5xFAD mice displayed immune ageing‐related signatures, including elevation of CD4 + FOXP3 + regulatory T cells (Tregs) and exhausted T cells expressing the inhibitory molecules PD‐1 and LAG‐3. Analysis of the plasma metabolome identified comorbidity‐associated signatures. Conclusion: Our study highlights accelerated immune ageing as a diet‐induced risk factor in AD.